Observed psychopathology in offspring of parents with major depressive disorder, bipolar disorder and schizophrenia. Issue 6 (23rd April 2020) - Sandstrom, A.; MacKenzie, L.; Pizzo, A.; Fine, A.; Rempel, S.; Howard, C.; Stephens, M.; Patterson, V. C.; Drobinin, V.; Van Gestel, H.; Howes Vallis, E.; Zwicker, A.; et al.
Abstract: Background: Children of parents with mood and psychotic disorders are at elevated risk for a range of behavioral and emotional problems. However, as the usual reporter of psychopathology in children is the parent, reports of early problems in children of parents with mood and psychotic disorders may be biased by the parents' own experience of mental illness and their mental state. Methods: Independent observers rated psychopathology using the Test Observation Form in 378 children and youth between the ages of 4 and 24 (mean = 11.01, s.d . = 4.40) who had a parent with major depressive disorder, bipolar disorder, schizophrenia, or no history of mood and psychotic disorders. Results: Observed attentional problems were elevated in offspring of parents with major depressive disorder, bipolar disorder and schizophrenia (effect sizes ranging between 0.31 and 0.56). Oppositional behavior and language/thought problems showed variable degrees of elevation (effect sizes 0.17 to 0.57) across the three high-risk groups, with the greatest difficulties observed in offspring of parents with bipolar disorder. Observed anxiety was increased in offspring of parents with major depressive disorder and bipolar disorder (effect sizes 0.19 and 0.25 respectively) but not in offspring of parents with schizophrenia. Conclusions: Our results suggest that externalizing problems and cognitive and language difficulties may represent a general manifestation of familial risk for mood and psychotic disorders, while anxiety may be a specific marker of liability for mood disorders. Observer assessment may improve early identification of risk and selection of youth who may benefit from targeted prevention.